The Role Of Study Habits In Academic Achievement: A Comparative Study Between Hostel-Living And Day Scholars - Muhammad, Israr; Jaffar, Romaisa; Rahim, Palwasha; Muhammad, Sabina Amir (Academic Journal of Psychology and Counseling, 2023)
Environmental conditions can have an impact on study habits, which affect academic achievement. Some students choose to live in dormitories (hostel-living students), while some opt to go home every day (day scholars). This research investigated differences in study habits and academic achievement between students living in hostels and at home. The sample was 213 undergraduate students at the University of Peshawar, Pakistan (102 day scholars and 112 hostel-living students). Study habit was measured by the Study Habits Inventory (SHI) developed by Jones & Slate (1990), and student academic achievement was measured by the Grade Point Average (GPA). The results showed that study habits significantly predicted academic achievement (β = 0.64, p<0.05). Hostel-living students have higher scores in study habits(t = -3.39, p<0.05) and academic achievement (t = -5.16, p<0.05) compared to day scholars. This shows that the dormitory environment encourages focused learning and contributes to academic achievement. Interventions for day scholars should target improved time management and accessible study space to enhance study habits and academic achievement.